Analisis Peran Kemitraan dalam Meningkatkan Pendapatan Petani : Studi Kasus Petani Kelapa Sawit di Desa Saham, Kabupaten Landak - Lokot Muda Harahap; Gracia Inri Sianturi; Julianty Samosir; Marta Marta; Putri Anita Lumbantoruan; Stefhani Gresia Simare-mare (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Oil palm farming is a major source of income for rural communities; however, smallholder farmers often face constraints such as limited capital, low access to technology, and unstable market conditions, which affect their income levels. This study aims to examine the role of partnerships in improving the income of oil palm farmers in Saham Village, Landak Regency. The research applies a qualitative descriptive approach based on a literature review, supported by secondary data from previous empirical studies related to farmers’ income and oil palm farming conditions in the study area. The findings indicate that partnerships contribute significantly to farmers’ income by facilitating access to production inputs, technical guidance, and more secure market channels. In addition, partnerships help stabilize selling prices and improve farmers’ bargaining position within the agribusiness value chain. The integration of farmers with stakeholders such as government institutions, cooperatives, plantation companies, and financial institutions enhances production efficiency and supports sustainable income improvement. Therefore, strengthening partnership schemes is essential to improve the welfare of smallholder oil palm farmers.